Role of Platelet Activation Factor in Patients with Hypersensitive Vasculitis, Autoimmune and Allergic Urticaria - Lishchuk-Yakymovych, Khrystyna; Chopyak, Valentyna; Mazepa, Nataliia; Pukalyak, Roman (SSP Modern Pharmacy and Medicine, 2024)
Cutaneous syndrome is a relevant issue not only among allergic diseases but also among autoimmune disorders. Urticaria is a widespread problem, as its prevalence among the population can reach up to 9%. The main goal of the article is to analyze the role of platelet-activating factor in patients with hypersensitive vasculitis, autoimmune, and allergic urticaria. Urticarial rash is at the intersection of allergic and autoimmune diseases, where is observed active immunopathogenetic influence of platelet-activating factor in the initiation and maintenance of systemic vasculitis, including hypersensitive/urticarial and cryoglobulinemic vasculitis Considering the significant role of this factor in the pathogenesis of hypersensitive vasculitis and allergic reactions, selective targeting of platelet-activating factor represents a promising therapeutic approach. These include platelet-activating factor receptor antagonists such as rupatadine and apafant, as well as platelet-activating factor acetylhydrolase inhibitors, enzymes responsible for platelet-activating factor degradation. Targeted intervention on platelet-activating factor holds promise for the improving the quality of life of patients with hypersensitive vasculitis, autoimmune disorders, and allergic urticaria.